Kupffer cell-targeting strategy for the protection of hepatic ischemia/reperfusion injury. (6th April 2021) - Dai, Qingqing; Jiang, Wei; Liu, Hu; Qing, Xin; Wang, Guobin; Huang, Fan; Yang, Zhilai; Wang, Chunhui; Gu, Erwei; Zhao, Hongchuan; Zhang, Jiqian; Liu, Xuesheng
Abstract: The aim of this study is to evaluate the effect of rare earth upconversion nanoparticles (UCNs) on hepatic ischemia reperfusion injury (IRI) and explore its possible mechanism. Hepatic IRI seriously affects the prognosis of patients undergoing liver surgery. Liver-resident Kupffer cells have been reported to promote IRI. Nanomedicines are known to be effective in the treatment of liver diseases, however, Kupffer cell-targeting nanomedicines for the treatment of IRI are yet to be developed. As potential bioimaging nanomaterials, UCNs have been found to specifically deplete Kupffer cells, but the underlying mechanism is unknown. In this study, we found that UCNs specifically depleted Kupffer cells by pyroptosis, while the co-administration of the caspase-1 inhibitor VX-765 rescued the UCN-induced Kupffer cell pyroptosis in mice. Furthermore, the pre-depletion of Kupffer cells by the UCNs significantly suppressed the release of inflammatory cytokines and effectively improved hepatic IRI. The rescue of the pyroptosis of the Kupffer cells by VX-765 abrogated the protective effect of UCNs on the liver. These results suggest that UCNs are highly promising for the development of Kupffer cell-targeting nanomedicines for intraoperative liver protection.